Flotsam and Jetsam: Art, Allegory, and Shipwreck in the Twenty-First Century (III) - Howard David Brian (American, British and Canadian Studies Journal)
This allegorical postcard is organized around two groups of photographs. The first group was the result of a joint collaboration with the Vancouver artist Scott Saunders, and it produced photographs which have peppered several of my previous texts published by American, British and Canadian Studies. The second is a series of photographs taken by Scott Saunders from the window of his apartment in Vancouver, in which he documents the street life constantly ebbing and flowing on the sidewalk below. The catalyst for bringing these two groups together was a photograph I took several years ago in Sambro, Nova Scotia (a small fishing village located just outside of the city of Halifax), depicting a forlorn sunken fishing vessel. The term “flotsam” is applied, according to the Oxford Reference Dictionary, to “the wreckage of a ship or its cargo floating on or washed up by the sea,” while “jetsam” describes the things or objects deliberately “thrown away, especially from a ship at sea and that float toward land.” Combined, these images of words and devastated human beings are caught in an apparently endless circulation of violence and contingency located at the heart of the urban fabric of a modernity bereft of any horizon of hope, redemption, or rescue.